Persepsi Masyarakat terhadap Peristiwa Bencana Banjir di Perumahan De Flamboyan Tanjung Selamat (Jurnal Ekonomi Bisnis dan Akuntansi, 2025)
Flooding is not a trivial issue, and many parties including the community and the government still need to pay special attention to this problem. Due to the river dam breach, flooding in De Flamboyan Housing, Tanjung Selamat disrupts government plans and economic growth, as well as daily activities of the community. The purpose of this research is to understand how the community perceives flooding in De Flamboyan Housing. This study utilizes a qualitative descriptive approach, with interviews, observations, and documentation as the data collection methods used in this research. The results of the study show that flooding caused the Tanjung Selamat river dam to collapse, inundating De Flamboyan housing and the surrounding areas.